Pengaruh Penghargaan Finansial, Pertimbangan Pasar Kerja, dan Lingkungan Kerja Terhadap Pemilihan Karir Sebagai Akuntan Pada Mahasiswa Akuntansi Di Jakarta - Zen Amalia; Achmad Fauzi; Mardi Mardi (ITB AAS INDONESIA Surakarta, 2021)
This study aims to determine whether there is an influence between financial rewards, labor market considerations, and work environment on career choices as accountants for accounting students in Jakarta by using a survey method. The population in this study were 518 accounting students at the University of Jakarta. The sampling technique used proportional random sampling so that the sample amounted to 226 students. The data analysis technique used is multiple regression analysis. Based on the results of the research that partially shows that there is a positive and significant influence between financial rewards and career choice as an accountant, job market consideration variables have a positive and significant influence on career choice as an accountant, work environment variables have a positive and significant effect on career choice as an accountant. . Meanwhile, simultaneously it shows that financial rewards, job market considerations, and work environment influence career choices as accountants. The magnitude of the influence of the variables of financial rewards, labor market considerations, and work environment on career choices as accountants is 42.4%, while the remaining 57.6% can be described by other variables not examined by the researcher. Keyword: Financial Rewards, Job Market Considerations, Work Environment, Career Choices as Accoutant